A retrospective cohort study on cassava food poisoning, Santa Cruz, Davao del Sur, Philippines, October 2015 - Johnette Peñas; Vikki Carr de los Reyes; Ma. Nemia Sucaldito; Denisse Lou Manalili; Herdie Hizon; Rio Magpantay (World Health Organization Regional Office for the Western Pacific, 2018)
Objective: On 2 October 2015, the Event-Based Surveillance and Response Unit of the Department of Health (DOH), Philippines received a report of foodborne illness cases in Santa Cruz, Davao del Sur. A team from DOH was sent to conduct an investigation to identify the implicated source and determine risk factors. Methods: A retrospective cohort study was done. A suspect case was defined as a previously well individual in Compound A, Santa Cruz who developed abdominal pain, headache, dizziness, diarrhoea or vomiting on either 1 or 2 October 2015. A confirmed case was a suspect case positive for cyanide in urine. Family members who prepared the food were interviewed. Urine specimens were collected to test for thiocyanate, and cassava tuber and soil samples were tested for cyanide and other chemicals. Result: Fourteen cases with two deaths were identified (case fatality ratio: 14%). All cases consumed cassava on 1 October 2015 except for one child who spat it out. Urine samples were all negative (36, 100%) for thiocyanate so there were no confirmed cases. The cassava sample had a cyanide level of 68.94 ug/g and was identified as bitter cassava, also known as a potentially dangerous kind. Insufficient food preparation was noted. In the retrospective cohort study, intake of cassava (RR = 208, 95% CI: 19.94-2169.32) was associated with the illness. Discussion: This study identified insufficiently processed cassava root crop as the source of the foodborne illness. The cassava consumed was the bitter variety that contains greater than 50 ug/g of hydrogen cyanide and requires thorough preparation before consumption. Community education was provided on identifying and preparing cassava appropriately.